2020
DOI: 10.1002/lary.28708
|View full text |Cite
|
Sign up to set email alerts
|

Optical Biopsy: Automated Classification of Airway Endoscopic Findings Using a Convolutional Neural Network

Abstract: Objectives/Hypothesis: Create an autonomous computational system to classify endoscopy findings. Study Design: Computational analysis of vocal fold images at an academic, tertiary-care laryngology practice. Methods: A series of normal and abnormal vocal fold images were obtained from the image database of an academic tertiary care laryngology practice. The benign images included normals, nodules, papilloma, polyps, and webs. A separate set of carcinoma and leukoplakia images comprised a single malignant-premal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Differentiation between benign and malignant laryngeal lesions that included 7 studies [23-27, 30, 32];…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differentiation between benign and malignant laryngeal lesions that included 7 studies [23-27, 30, 32];…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of AI accuracy of white light endoscopy (4 studies) [23, 27, 30, 32] with NBI method (3 studies) [24-26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The skill of deep learning of surgical navigation is expected to be applied to assistant clinicians in endoscopic examinations. In another study[ 49 ], the authors created an autonomous computational system to classify endoscopy findings and showed that autonomous classification of endoscopic images with AI technology is possible. The overall accuracy for the benign classifier was 80.8%.…”
Section: Deep Learning Driven Colorectal Lesion Analysismentioning
confidence: 99%
“…In one previous study, the binary classifier distinguished benign and malignant-premalignant lesions with an overall accuracy of 93.0%. 18 A sensitivity of 89% and a specificity of 99.33% were achieved for the malignancy by autonomous classification of endoscopic images with artificial intelligence technology. 19 However, the studies mentioned above were both carried out in a single center.…”
Section: Introductionmentioning
confidence: 99%